Analysis Of Basic Technical Abilities Of Futsal Players Aged 10-13 Years At Merpati Muda Futsal School - Dinovanto Acarya Putra; Agus Wiyanto; Buyung Kusumawardana (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Futsal is a sport that demands high levels of speed, coordination, agility, and mastery of basic technical skills, particularly for players in the early developmental stages. However, training programs for young futsal players are often implemented without being preceded by an objective assessment of their basic technical abilities. This condition may lead to training that is less effective and not aligned with the developmental needs of the athletes. Therefore, it is important to analyze the basic technical abilities of young futsal players as a foundation for designing appropriate and systematic training programs. This study aims to analyze the basic technical abilities of futsal players aged 10–13 years at the Merpati Muda Futsal School in Tangerang City. This research employed a quantitative descriptive research design. The subjects of the study were futsal players aged 10–13 years who were actively training at the Merpati Muda Futsal School. Data were collected through observation, documentation, and standardized basic futsal skills tests. The instrument used in this study was the Young Futsal Specific Test Battery (YFSTB), which consists of five components: dribbling, passing, ball control, zigzag dribbling, and shooting. The collected data were analyzed using descriptive statistical techniques to describe the level of players’ basic technical abilities. The results of this study are expected to provide an objective and comprehensive profile of the basic technical abilities of early-age futsal players. These findings can be used as a reference for coaches and trainers in evaluating athletes’ technical skills and in planning age-appropriate, targeted, and effective training programs. In addition, this study is expected to contribute to the development of early-age futsal coaching, particularly in optimizing the technical development of young players